The (in)dependence of articulation and lexical planning during isolated word production. Issue 3 (15th March 2016) - Buz, Esteban; Jaeger, T. Florian
ABSTRACT: The number of phonological neighbours to a word (PND) can affect its lexical planning and pronunciation. Similar parallel effects on planning and articulation have been observed for other lexical variables, such as a word's contextual predictability. Such parallelism is frequently taken to indicate that effects on articulation are mediated by effects on the time course of lexical planning. We test this mediation assumption for PND and find it unsupported. In a picture naming experiment, we measure speech onset latencies (planning), word durations, and vowel dispersion (articulation). We find that PND predicts both latencies and durations. Further, latencies predict durations. However, the effects of PND and latency on duration are independent: parallel effects do not imply mediation. We discuss the consequences for accounts of lexical planning, articulation, and the link between them. In particular, our results suggest that ease of planning does not explain effects of PND on articulation.